IMPACT OF FLEXIBLE WORK, TECHNOSTRESS ON PERFORMANCE WITH SUPERVISOR SUPPORT AS A MODERATING VARIABLE - Turmudi; Meliala, Janita S; Widokarti, Joko Rizkie (Universitas prof. Dr. Moestopo (Beragama), 2025)
After the COVID-19 pandemic, many organizations asked employees to return to conventional work arrangements. However, the worsening air quality in DKI Jakarta led the government to implement a work from home policy for civil servants. Concerns have arisen about the performance of civil servants if work from home a form of flexible working arrangement, is implemented permanently. Thus, this research is performed to investigate the influence of flexible working arrangement on performance, incorporating technostress as an independent variable and supervisor support as a moderating variable. Using a quantitative method, 507 civil servants in DKI Jakarta who experienced flexible working arrangement for at least six months participated in the study. Data were collected via an online questionnaire and analyzed using multiple regression and moderation regression methods. The results revealed that flexible working arrangement positively and significantly influences employee performance. Technostress negatively and significantly affects performance. Supervisor support strengthens the positive impact of flexible working arrangement on performance, but its moderating effect on technostress is non-significant. Thus, while flexible working arrangement improves performance, and technostress hinders it, the negative impact of technostress can be mitigated by supervisor support, reducing its significance. This research underscores the importance of balancing flexible work arrangements with adequate supervisor support to enhance civil servants' performance.